Association of STAT-3 rs1053004 and VDR rs11574077 With FOLFIRI-Related Gastrointestinal Toxicity in Metastatic Colorectal Cancer Patients - De Mattia, Elena; Cecchin, Erika; Montico, Marcella; Labriet, Adrien; Guillemette, Chantal; Dreussi, Eva; Roncato, Rossana; Bignucolo, Alessia; Buonadonna, Angela; D’Andrea, Mario; Coppola, Luigi; Lonardi, Sara; et al. (Frontiers in Pharmacology, 2018)
Pharmacogenomics has largely been applied to the personalization of irinotecan-based treatment, focusing mainly on the study of genetic variants in adsorption, distribution, metabolism, and excretion (ADME) genes. The transcriptional control of ADME gene expression is mediated by a set of nuclear factors responding to cancer-related inflammation, which could have pharmacological implications. The aim of the present study was to uncover novel genetic predictors of neutropenia and gastrointestinal toxicity risk among 246 haplotype-tagging polymorphisms in 22 genes encoding inflammation-related cytokines and transcriptional regulators of ADME genes. The study comprised overall more than 400 metastatic colorectal cancer (mCRC) patients treated with first-line FOLFIRI, grouped in a discovery and a replication cohorts. A concordant protective effect of STAT-3 rs1053004 polymorphism against the risk of grade 3-4 gastrointestinal toxicity was observed in both the cohorts of patients (OR=0.51, p=0.045, q=0.521 and OR=0.39, p=0.043, respectively). VDR rs11574077 polymorphism was demonstrated to affect both irinotecan biliary index and glucuronidation ratio by a pharmacokinetic analysis. This effect was consistent with an increased risk of grade 3-4 gastrointestinal toxicity in the discovery cohort (OR=4.46, p=0.010, q=0.305). The association was not significant in the replication cohort (OR=1.44, p=0.601). These findings suggest an effect of STAT-3 and VDR polymorphisms on FOLFIRI-related gastrointestinal toxicity. If prospectively validated as predictive markers, they could be used to improve the clinical management of mCRC.